Impaired Brain Mitochondrial Bioenergetics in the Ts65Dn Mouse Model of Down Syndrome Is Restored by Neonatal Treatment with the Polyphenol 7,8-Dihydroxyflavone - Daniela Valenti; Fiorenza Stagni; Marco Emili; Sandra Guidi; Renata Bartesaghi; Rosa Anna Vacca (Antioxidants, 2021)
Down syndrome (DS), a major genetic cause of intellectual disability, is characterized by numerous neurodevelopmental defects. Previous in vitro studies highlighted a relationship between bioenergetic dysfunction and reduced neurogenesis in progenitor cells from the Ts65Dn mouse model of DS, suggesting a critical role of mitochondrial dysfunction in neurodevelopmental alterations in DS. Recent in vivo studies in Ts65Dn mice showed that neonatal supplementation (Days P3–P15) with the polyphenol 7,8-dihydroxyflavone (7,8-DHF) fully restored hippocampal neurogenesis. The current study was aimed to establish whether brain mitochondrial bioenergetic defects are already present in Ts65Dn pups and whether early treatment with 7,8-DHF positively impacts on mitochondrial function. In the brain and cerebellum of P3 and P15 Ts65Dn pups we found a strong impairment in the oxidative phosphorylation apparatus, resulting in a deficit in mitochondrial ATP production and ATP content. Administration of 7,8-DHF (dose: 5 mg/kg/day) during Days P3–P15 fully restored bioenergetic dysfunction in Ts65Dn mice, reduced the levels of oxygen radicals and reinstated the hippocampal levels of PGC-1α. No pharmacotherapy is available for DS. From current findings, 7,8-DHF emerges as a treatment with a good translational potential for improving mitochondrial bioenergetics and, thus, mitochondria-linked neurodevelopmental alterations in DS.